Editorial: Volume 2 - Issue 1 - Cihan Cobanoglu; Serdar Ongan (Journal of Global Business Insights, 2017)
The National Academies defines interdisciplinary research as “a mode of research by teams or individuals that integrates information, data, techniques, tools, perspectives, concepts, and/or theories from two or more disciplines or bodies of specialized knowledge to advance fundamental understanding or to solve problems whose solutions are beyond the scope of a single discipline or area of research practice.” The fields of business and economics are very suitable for interdisciplinary research. For this reason, we decided to develop and publish an international double blind peer reviewed journal - International Interdisciplinary Business- Economics Advancement (IIBA) Journal - to feature business and economics research that spans more than one discipline. The International Interdisciplinary Business Economics Advancement (IIBA) Journal aims to publish new ideas, research and results concerning all aspects of Business and Economics, and to discuss the practical challenges encountered in the field as well as the solutions adopted. Hence, it will be a platform where numerous disciplines converge. For this reason, we invite scholars from different academic disciplines to collaborate with scholars from other disciplines, tackle issues to solve current and future problems, contribute to the body of knowledge and share their views and research findings. IIBA Journal also welcomes any conceptual papers in addition to contributions towards theory testing and development which will help future empirical studies. It is with a great pleasure that we welcome you to the third issue of the IIBA Journal. This issue presents five excellent contributions. The first paper by Richard Martin offers the concept of leader's psychological resilience (PsyRes) consisting of three major components: emotional intelligence, authenticity, and meaning in life. The second paper by Gulseren Yurcu, Zeki Akıncı and Murad Alpaslan Kasalak reveals the effects of tourism students’ personality traits on leisure motivation and social wellbeing. In addition, the third paper by Necdet Saglam illustrates the history of accounting and auditing in Turkey. In the fouth paper, Cem Berk and Niyazi Berk analyzes the EU insurance system and Turkish insurance sector comparatively in light of the Solvency II regulation. Last but not least, in the fifth paper, Carolin Lusby focuses on the American and Macau student perceptions towards working in the tourism and hospitality industry. Please provide feedback for the articles that are published in IIBA Journal. We also invite you to submit an article for IIBA Journal.